PENERAPAN MODEL RASIONAL-KOMPREHENSIF DALAM PERENCANAAN BERBASIS SEKOLAH DI SMK NEGERI 1 KUALA KAPUAS - Trisna; Ramadhan, Fitriyadi; Sulistiyana; Suhaimi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the Rational–Comprehensive Model in school-based planning at SMK Negeri 1 Kuala Kapuas, particularly in the preparation of the School Work Plan (RKS) and the School Activity and Budget Plan (RKAS), as well as its impact on the effectiveness and efficiency of vocational education programs. The research employed a descriptive qualitative approach, with data collected through in-depth interviews, participatory observation, and document analysis. The research participants included the principal, vice principals, teachers, administrative staff, and representatives from industry partners. The findings indicate that the Rational–Comprehensive Model has been implemented through systematic stages, including needs assessment based on school quality reports and performance data, analysis of alternative programs, priority setting, implementation, monitoring, and evaluation. The planning process has become more evidence-based, participatory, and aligned with industry demands. Key priority programs include student internships (PKL), competency certification, vocational competency examinations, teacher professional development, and the procurement of practical training equipment. Despite challenges such as limited financial resources, time constraints for teachers, and performance-based evaluation limitations, the application of this model has improved program effectiveness by ensuring that activities are goal-oriented and needs-based. It has also enhanced budget efficiency through clear prioritization. Overall, the Rational–Comprehensive Model serves as a strategic approach to strengthening accountability, improving educational quality, and increasing the relevance of vocational education to labor market demands.